2001
DOI: 10.1002/jmv.2049
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and severity of infections caused by subgroup A and B respiratory syncytial virus in children in Southeast Brazil

Abstract: The frequency and severity of infections caused by respiratory syncytial virus (RSV) were assessed in children <2 years of age seen at the emergency department. The frequency of RSV detection in the clinical virology laboratory during the past 3 years was also analyzed retrospectively. RSV was found in 21.6% (188/869) of the samples collected from children seen at the emergency department and was found to be more frequent during the autumn, being less frequent or negligible by midwinter. RSV subgroups A and B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
33
1
30

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 25 publications
(30 reference statements)
7
33
1
30
Order By: Relevance
“…From the total of HRSV positive results, 80% (12/15) were obtained from children under six months of age, agreeing with data found in the literature (4,13,23,26). Also it was observed that the number of positive cases of HRSV and ARD decreased significantly with the increase of age (data not shown).…”
supporting
confidence: 90%
See 3 more Smart Citations
“…From the total of HRSV positive results, 80% (12/15) were obtained from children under six months of age, agreeing with data found in the literature (4,13,23,26). Also it was observed that the number of positive cases of HRSV and ARD decreased significantly with the increase of age (data not shown).…”
supporting
confidence: 90%
“…In conclusion, our results show that in Botucatu city, representing a large area of São Paulo state inlands, HRSV occurrence has a similar pattern of that observed in other cities of Brazil's southeast (4,27).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Esta característica também foi observada no Brasil, nas cidades do Rio de Janeiro 52 , São Paulo 53 e Ribeirão Preto 54 , onde o período epidêmico do VRS acontece no primeiro semestre do ano, com variações nos meses de pico, conforme a localidade.…”
Section: Imunização Passiva Para Vírus Respiratório Sincicial (Vrs)unclassified